LEADERSHIP DECAPITATION: ISRAELI COUNTERTERRORISM POLICY AND THE PALESTINIAN ISLAMIC JIHAD - Scott Nicholas Romaniuk (European Scientific Journal, ESJ, 2014)
The specific conditions under which terrorist decapitation results in the dissolution of the terrorist group and other short- and long-term effects of this tactic are some of the critical questions that require further attention given that states such as the US and Israel are sure to employ this tactic to considerable means in the near and distant future, particularly given the vague framework of the unending nature of War on Terror (WOT) that has helped produce numerous loopholes that enable the undertaking of precision acts that are often characterized as “discriminate wars” (Schmitt, 2005). In this paper I argue that in spite of short-term success for Israel, the PIJ was able to reorient itself from the shock of losing its leader. This is demonstrated not only by it ongoing service to violent terrorist means, but also due in part to its increased use of suicide bombings that have result in a greater loss of life since the events of 1995 as well as the escalation of suicide terrorism (ST) by other terrorist groups and organizations in the region and further abroad.